2022
DOI: 10.1111/ced.15351
|View full text |Cite
|
Sign up to set email alerts
|

Long-term management options for sea urchin injury: a case series

Abstract: In the UK, sea urchin-related injuries (SUIs) most commonly present in returning travellers. Delayed complications mainly affect the skin but nerves, tendons, joints and bones may also be involved. The management of chronic reactions may be challenging and a variety of approaches have been described. Surgical measures are often undertaken, particularly when retained spines are suspected. We demonstrate, through three cases presenting in the UK with chronic SUIs, that conservative management, surgery and intral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The SUI was appropriately treated by removal of the spines, 4 but the application of lime juice caused the skin changes seen in our patient. In nonmedical settings such as beach resorts, use of lime juice or other acidic substances to attempt to dissolve the spines is believed to be an effective method.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…The SUI was appropriately treated by removal of the spines, 4 but the application of lime juice caused the skin changes seen in our patient. In nonmedical settings such as beach resorts, use of lime juice or other acidic substances to attempt to dissolve the spines is believed to be an effective method.…”
mentioning
confidence: 72%
“…In nonmedical settings such as beach resorts, use of lime juice or other acidic substances to attempt to dissolve the spines is believed to be an effective method. Removal of the spines is crucial to prevent development of chronic granulomatous reactions, 4 but use of acidic substances such as lime juice should be avoided. Use of nonphotosensitizing antiseptic agents may be more appropriate.…”
mentioning
confidence: 99%
“…As shown by our patient’s case, a sea urchin spine that is not embedded near-critical regions might not require surgical intervention. We suspect that in many cases, because symptoms from one or a few embedded sea urchin spine tips improve rather quickly, they are not removed and are ultimately deemed innocuous [ 31 , 58 ]. Similarly, in our patient, despite the presence of an embedded spine eight years after injury, he reported no pain or discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the investigator reported that the embedded sea urchin spines were detected on plain or standard radiographs, though they were very faint. In cases such as these, radiographs with 'soft tissue windows' or with the capacity of other digital enhancements, or ultrasonography, are the next steps in the diagnostic imaging workup of sea urchin injuries [10,[28][29][30][31][32]. Computed tomography (CT) scanning in cases of deeply embedded spines can be more useful than plain radiography and is also superior to magnetic resonance (MR) imaging for detecting embedded sea urchin spines [10].…”
Section: Chemical Composition and Detection In Clinical Imagingmentioning
confidence: 99%